Pirfenidone suppressed triple‐negative breast cancer metastasis by inhibiting the activity of the TGF‐β/SMAD pathway. Issue 3 (18th January 2023) - Luo, Daiqin; Zeng, Xianlin; Zhang, Shuling; Li, Daohong; Cheng, Zhimei; Wang, Yun; Long, Jinhua; Hu, Zuquan; Long, Shiqi; Zhou, Jing; Zhang, Shuai; Zeng, Zhu
Abstract: Among breast cancer patients, metastases are the leading cause of death. Despite decades of effort, little progress has been made to improve the treatment of breast cancer metastases, especially triple‐negative breast cancer (TNBC). The extracellular matrix plays an important role in tumour growth and metastasis by causing its deposition, remodelling, and signalling. As we know, the process of fibrosis results in excessive amounts of extracellular matrix being deposited within the cells. So, it will be interesting to study if the use of anti‐fibrotic drugs in combination with conventional chemotherapy drugs can produce synergistic antitumor effects. In this study, we assessed the efficacy of Pirfenidone (PFD), an FDA‐approved medication for the treatment of idiopathic pulmonary fibrosis, on TNBC cells as well as its anti‐tumour effects in xenograft tumour model. PFD inhibited in a dose‐dependent manner breast cancer cell proliferation, migration, and invasion, while promoted their apoptosis in vitro. PFD also suppressed TGF‐β‐induced activation of Smad signalling pathway and expression level of EMT‐inducing transcription factors (e.g. SNAI2, TWIST1, ZEB1) as well as the mesenchymal genes such as VIMENTIN and N‐Cadherin. On the contrary, the expression level of epithelial marker gene E‐Cadherin was up‐regulated in the presence of PFD. In vivo, PFD alone exerted a milder but significant anti‐tumour effect than the chemotherapy drug nanoparticle albumin‐bound paclitaxel (nab‐PTX) did in the breast cancer xenograft mouse model. Interestingly, PFD synergistically boosted the cancer‐killing effect of nab‐PTX. Furthermore, Our data suggest that PFD suppressed breast cancer metastasis by inhibiting the activity of the TGFβ/SMAD pathway.